Apostolo Zeno: Poesie drammatiche, Parte I, Volume 2: Parte I: Venezia e oltre Vol. 2: da Il Venceslao (1703) ad Alessandro Severo (1717) - Noe, Alfred (2021)
This is the first part of a critical edition of the complete dramatic works by Apostolo Zeno. Vol. I.2 offers 9 librettos: Il Venceslao, Aminta, Pirro, Il Teuzzone, L'Amor generoso, Atenaide, Scipione nelle Spagne, Merope, Alessandro Severo. Parte I Volume 1: https://e-book.fwf.ac.at/o:1587 Parte I Volume 2: https://e-book.fwf.ac.at/o:1588